The Existence of Pretrial Institutions In The Enforcement Of Criminal Law - Ko Triskie Narendra; Didik Endro Purwoleksono; Taufik Rachman (Faculty of Law, Universitas Pekalongan, 2023)
Milestone Born Based on the Constitutional Court Decision: 21/PUU-XII/2014 dated April 28, 2015, the authority of the Pretrial institution has increased by conducting an examination of the Investigator's actions in issuing a letter of determination of suspects, searches, and seizures coupled with the legality or absence of arrest and/or detention, termination of investigation or termination of prosecution upon request for the upholding of law and justice, and requests for compensation or rehabilitation. In legal practice, there are several Decisions that do not reflect the implementation of criminal procedure law in accordance with the scope of pretrial and create new authority in pretrial.The norms of authority in the Criminal Procedure Code provide limitations/limitations that cannot be deviated by law enforcement, if law enforcement exercises its authority not based on laws and regulations, then law enforcement actions can be categorized as unlawful acts. Based on Article 24C paragraph 1 of the Constitution of the Republic of Indonesia of 1945 (third amendment), the Constitutional Court is a high state institution within the scope of judicial power (judicial) and the authority of the Constitutional Court is one of which is to test the Law against the 1945 Constitution. Suppose a decision that grants the application, has an impact on the invalidity of a norm and does not have binding legal force, then by itself, the decision cannot be separated from the Erga Omnes Principle which has legally binding force on all components of the nation, so all parties must submit and obey the decision ( Syukri Asy'ari, 2013). In legal practice, there are several Decisions that do not reflect the implementation of criminal procedure law in accordance with the scope of pretrial and create new authority in pretrial so that how does pretrial exist in the enforcement of criminal law